Effects of the High Temperature on the Physical and Chemical Properties of Some Public Health Insecticide Formulations - AKSOY, ABDURRAHMAN; YAVUZ, OGUZHAN; GUVENC, DILEK; KURSAD DAS, YAVUZ (Asian Journal of Chemistry, 2010)
Insecticides are manufactured, formulated and packaged to specific standards for safe and effective vector control. Sometimes the insecticide products can break down and lose their active ingredients under storage conditions (especially high temperature). In this study, 11 different insecticide formulations were stored in 50 mL coex bottles (same as an original package) at 54ºC during 14 d. The formulations contained 1 organophosphate (temephos) and 6 synthetic pyrethroids (α-cypermethrin, δ-methrin, cypermethrin, cyfluthrin, cyphenothrin and permethrin) alone or combined with knock down agent tetramethrin and synergist agent piperonyl butoxide. Formulation type of all formulations was emulsifiable concentrate. Density, appearance, colour and pH of the formulations were determined as the physical parameters at the beginning and end of the storage period. The chemical analysis of the samples was made by gas chromatography equipped with flame ionization detector at the beginning and 14th day. At the end of the study, physical and chemical features of the used formulations did not change under the high temperature (54ºC) during 14 d. The formulations used in the study are resistant to high temperature and they may safely use for a long time under the normal storage conditions. Also, the formulations can be effective to the target organisms in the tropics or in temperate climates. But, we defined that, accelerated stability tests are not satisfactory in the field conditions and long term stability tests, especially 2 years or more and biological efficacy tests should be performed additionally.